Study guides

☆☆

Q: 9a 3b take away 8a - 3b?

Write your answer...

Submit

Still have questions?

Related questions

9a - 8a = a

The given terms can be simplified to: a -b

9a + 3b - 11a - 4b = -2a -b

13

9a + 7b *remember to look and understand the letters!*

12

9a-a = 19+7a 8a = 19+7a 8a - 7a = 19 + 7a - 7a 1a = 19 a = 19

3(3a+b)

3a + 4b - (-6a) - 3b? There is no equivalent because you did not make it an equality. However you could combine the numbers... 3a + 4b +6a -3b = 9a + 1b

9a. You take 11 a's: a a a a a a a a a a a and then take away two (minus a, minus a): a a a a a a a a a X X

KCPS-AM (1150 kHz), Burlington, Davenport and Rock Island-Moline, M-Sa 8a-11a (live M-F)WCKG-AM (1530 kHz), Chicago, M-F 8a-11a (live)WCRA-AM (1090 kHz), Effingham, M-F 8a-11a (live)WGIL-AM (1400 kHz), Davenport, M-F 9a-12nWINI-AM (1420 kHz), Sparta, M-F 9a-12n, Sa 5a-8aWKAN-AM (1320 kHz), Kankakee, M-F 8a-11a (live)WLPO-AM (1220 kHz), Oglesby, Su 12n-3p, M-F 10a-12nWLRB-AM (1510 kHz), Macomb, M-Sa 8a-11a (live M-F)WMBD-AM (1470 kHz), Peoria, M-F 8a-11a (live)WRPW-FM (92.9 MHz), Normal, M-F 8a-11a (live), Sa 5a-8aWTAD-AM (930 kHz), Quincy, M-F 4p-7pWTAX-AM (1240 kHz), Springfield, M-F 8a-11a (live)WTRH-FM (93.3 MHz), Ramsey, M-F 8a-11a (live)WZUS-FM (100.9 MHz), Decatur, M-F 9a-12n, Sa 5a-8a

6 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -3

People also asked